Applied Big Data Driven Study on Shock Absorption and Tolerance Bands of Staple Food Commodities Price Volatility in East Java - Firman Sihol Parningotan; Avi Aviliani; Jonathan Herawan; Matthew Kartawinata (INDEF - Institute for Development of Economics and Finance, 2025)
This study investigates the day-to-day volatility dynamics of five staple food commodities in East Java which are Red Bird’s Eye Chili Pepper, Medium Rice, Bendera Powdered Milk, Free-Range Chicken Meat, and Commercial Chicken Eggs. By utilizing daily price data from January 1, 2021, to February 2, 2025, collected via big-data scraping of a government price monitoring website. A GARCH model with Student-t innovations is fitted to each return series, from which one-day 95% Value-at-Risk (VaR) thresholds are derived to establish an evidence-based